Estetika Bentuk Udeng Model Pacul Gowang pada Tata Rias Pengantin Laki-Laki œPutri Jenggolo Sidoarjo - Ni'mah, Ulfa (Journal of Beauty and Cosmetology (JBC), 2020)
Putri Jenggolo bridal makeup was created in 1985 where the groom wore udeng as a head cover. This study aimed to describe the development of udeng shape in Putri Jenggolo bridal makeup, describe the aesthetic of Pacul Gowang model on Putri Jenggolo bridal makeup, and find out the different forms of Pacul Gowang udeng and East Java udeng. This study used qualitative research approach. Data were collected using interview and documentation. The research setting was in Magersari, Wonoayu, Sidoarjo. The key informants were Sidoarjo culturist, Association of HARPI Melati in Sidoarjo, and the creator of udeng. The obtained data were analyzed using aesthetic analysis theory that included data reduction, data presentation, and conclusion. The results showed that, in 1985, the groom's makeup used a Surabaya-style udeng with Sidamukti motif which was later refined its top and made as Pacul Gowang shape, of which it was used as the bride-style udeng of Putri Jenggolo bride in Sidoarjo, East Java. This Pacul Gowang udeng had an aesthetic value from its look and message, especially the existing variety of Sidoarjo batik motifs. The batik motif had the meaning of fertility and peace, graceful and dignified, and firmness and courage. The details of Pacul Gowang udeng shape covering spiky bucen, blunt bucen, gowang head cover, udeng knot, 2 upright cungkup, nape cover, and Sidoarjo batik motifs became the distinguishing features of other East Java udeng models.Keywords: Bridal makeup, aesthetic, udeng, ornamental variety